Synthesis of bio-lubricant through the esterification of oleic acid and trimethylolpropane catalysed by sulfated tin (ii) oxide - Loo, Mei Soon (2014)
Bio-lubricant has been proclaimed as a renewable alternative to mineral oil based lubricant due to the growing concern to the environmental impact and sustainability issue of the mineral oil based lubricant. Synthetic esters produced from the esterification of polyols and fatty acids are the bio-lubricant that can replace the mineral oil based lubricants in several applications. In this study, the synthesis of bio-lubricant, trimethylolpropane (TMP) oleate, using sulfated tin (II) oxide was carried out. TMP oleate is most common and widely used in hydraulic fluids. The heterogeneous sulfated tin (II) oxide has been chosen as catalyst because of the shortcomings of the homogeneous catalysts such as difficulty to be separated from the products and reused. The sulfated tin (II) oxide was synthesized by precipitation followed by impregnation and characterized for its’ physicochemical properties. The catalytic activity was examined through the esterification of TMP and oleic acid (OA) under constant rate of stirring of 800rpm, 0.3 wt. % catalyst with particle diameter of, dp≤63 μm to eliminate the resistance of external and internal diffusion. The molar ratio of TMP to oleic acids was varied from 1:2.7-1:3.3 and reaction temperature was varied from 120oC-180oC. The TMP oleate synthesized was tested for its total acid number and viscosity. The results indicated that the highest conversion of OA, 91.2% was achieved at temperature of 180oC and the molar ratio of TMP: OA was 1:2.7. Apparently, the reaction temperature has more significant effect on the conversion of OA as compared to molar ratio of reactant, verifying that the reaction is controlled by surface reaction. The catalyst synthesized in this work is expected to provide a simpler and cheaper separation process with the catalyst reuse, reduced waste generation, and increase in yield of TMP oleate at optimum parameters.